2010
DOI: 10.4103/0250-474x.65014
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of liposomal formulation of pilocarpine nitrate

Abstract: Prolonged release drug delivery system of pilocarpine nitrate was made by optimizing thin layer film hydration method. Egg phosphatidylcholine and cholesterol were used to make multilamellar vesicles. Effects of charges over the vesicles were studied by incorporating dicetylphosphate and stearylamine. Various factors, which may affect the size, shape, encapsulation efficiency and release rate, were studied. Liposomes in the size range 0.2 to 1 µm were obtained by optimizing the process. Encapsulation efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…mPEG 2000 -DSPE was incorporated for PEGylation which would further improve pharmacokinetic profile of formulation. The use of negatively charged lipid (DSPG) in optimized formulation is rationalized as it leads to improved entrapment efficiency by increasing the entrapped volume (Rathod & Deshpande, 2010). Various parameters like ammonium sulfate concentration, loading time, loading temperature, etc., were optimized to maximize drug loading in the liposomes.…”
Section: Preparation and Characterization Of Liposomesmentioning
confidence: 99%
“…mPEG 2000 -DSPE was incorporated for PEGylation which would further improve pharmacokinetic profile of formulation. The use of negatively charged lipid (DSPG) in optimized formulation is rationalized as it leads to improved entrapment efficiency by increasing the entrapped volume (Rathod & Deshpande, 2010). Various parameters like ammonium sulfate concentration, loading time, loading temperature, etc., were optimized to maximize drug loading in the liposomes.…”
Section: Preparation and Characterization Of Liposomesmentioning
confidence: 99%
“…Studies have shown that liposomes are also efficient carriers of amphiphilic drugs . Liposomes enhance the corneal permeability of lipophilic, hydrophilic as well as amphiphilic drugs due to their ability to come in close contact with cornea and conjunctiva Dharma et al, 1986) and increase the extent of corneal uptake by prolonging the corneal contact time (Rathod & Deshpande, 2010). Additionally, liposomes are completely biodegradable and relatively nontoxic.…”
Section: Conventional Liposomes: Modifications To Meet the Challengesmentioning
confidence: 99%
“…In general, charged liposomes resist aggregation and fusion better compared to uncharged liposomes and positively charged liposomes provide greater duration of action and higher drug delivery compared to negatively charged liposomes Weissmann et al, 1985;Rathod & Deshpande, 2010). This is because positively charged liposomes intimately interact with negatively charged cornea leading to prolonged residence time (Law et al, 2000).…”
Section: Surface Charge and Size Of Liposomesmentioning
confidence: 99%
“…Liposomes as Vaccine Adjuvants: Liposomal vaccines can be made by associating microbes, soluble antigens, cytokines, or DNA with liposomes, the latter stimulating an immune response on expression of the antigenic protein 10 . Liposomes encapsulating antigens are subsequently encapsulated within alginate lysine microcapsules to control the antigen release and to improve the antibody response 11 .…”
Section: Applicationsmentioning
confidence: 99%